The Lombard Church. Studies on the Ecclesiastical history of the Po region (14th-15th centuries) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
This essay points out some fundamental traits illustrated by Giorgio Chittolini's research on Lombardy's ecclesiastical institutions in the 14th and 15th centuries: moderate attention to the needs for religious reform, strong influence of the local society of villages and towns, and the presence of a large clergy. The research is based on a wealth of notarial documentation.
Keywords: Giorgio Chittolini; Middle Ages; Lombardy; Ecclesiastical Institutions; Notarial Sources